FT3/FT4 ratio is correlated with all-cause mortality, cardiovascular mortality, and cardiovascular disease risk: NHANES 2007-2012 - Lang, Xueyan; Li, Yilan; Zhang, Dandan; Zhang, Yuheng; Wu, Nilian; Zhang, Yao (Frontiers in Endocrinology, 2022)
Background: Thyroid hormones play a vital role in maintaining the homeostasis of the cardiovascular system. The FT3/FT4 ratio can be used to evaluate the rate of T4-to-T3 conversion, reflecting the peripheral sensitivity of thyroid hormones. There is no study to investigate its relationship with death and cardiovascular disease (CVD) in the general population. Methods: This retrospective cohort study involved 8,018 participants with measured thyroid function and no prior thyroid disease who participated in the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2012. Mortality status was determined by routine follow-up using the National Death Index through December 31, 2015. Results: During a median of 87 months of follow-up, we observed 699 all-cause deaths, including 116 cardiovascular deaths. In multivariate adjusted models, higher free thyroxine (FT4) was linked to increased all-cause mortality (HR, 1.15 per SD; 95% CI, 1.09-1.22), cardiovascular mortality (HR, 1.18 per SD; 95% CI, 1.01-1.39), and CVD risk (HR, 1.17 per SD; 95% CI, 1.08-1.27). Higher free triiodothyronine (FT3) was linked to decreased all-cause mortality (HR 0.81 per SD; 95% CI, 0.70-0.93). Higher FT3/FT4 ratio was linked to decreased all-cause mortality (HR, 0.77 per SD; 95% CI, 0.69-0.85), cardiovascular mortality (HR, 0.79 per SD; 95% CI, 0.62-1.00), and CVD risk (HR, 0.82 per SD; 95% CI, 0.74-0.92). The FT3/FT4 ratio stratified findings were broadly consistent with the overall results. Conclusions: FT3, FT4, and the FT3/FT4 ratio were all independent predictors of all-cause death. FT4 and the FT3/FT4 ratio, but not FT3, were independent predictors of cardiovascular mortality and CVD risk. Along with FT3 and FT4, we should pay equal attention to the FT3/FT4 ratio in the general population.